2009
DOI: 10.1590/s0102-261x2009000100002
|View full text |Cite
|
Sign up to set email alerts
|

Análise da variação dos elementos do campo de gravidade na região do Aqüifero Guarani a partir dos dados GRACE

Abstract: ABSTRACT. This work estimates the variation of the gravity field elements in a period of two years and three months -April 2002 to July 2004 -using the GRACE mission data in the Guarani aquifer region; these changes are the sum of all the gravity changes that are caused by variations from mass distribution of the Earth's surface and by the deformation of the solid Earth in response to these mass variations. The solutions have been calculated only from the disturbances of the satellite orbits and do not depend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Therefore, any alteration on the Bouguer anomaly might be due to fluid storage variation. Bomfim and Molina (2009) showed that the vertical uncertainty on the solutions to the gravitational field using GRACE data are on the millimeter scale, which can be considered precise enough to the present paper, because the observed alterations on the water table level are of such order of magnitude.…”
Section: Data Acquisition and Processingmentioning
confidence: 62%
See 2 more Smart Citations
“…Therefore, any alteration on the Bouguer anomaly might be due to fluid storage variation. Bomfim and Molina (2009) showed that the vertical uncertainty on the solutions to the gravitational field using GRACE data are on the millimeter scale, which can be considered precise enough to the present paper, because the observed alterations on the water table level are of such order of magnitude.…”
Section: Data Acquisition and Processingmentioning
confidence: 62%
“…Another more sensitive method, such as field gravimetry, would be needed to detect time variations on the gravitational field that could be imparted by any fluid displacement over time. Bomfim and Molina (2009) employed the residual anomalies method to estimate the variations on the gravitational field and validated it through comparison of gravimetric inversions. They did not compare their conclusions to meteorological values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a plastic deformation of the crust takes place and can be observed through calculation of the Stokes coefficients provided by GRACE mission [26]. Therefore, it is possible to foresee the future of the aquifer based on the balance between recharging and exploration.…”
Section: Different Approaches On the Investigation Of Ground Water 44mentioning
confidence: 99%